1995
DOI: 10.1099/0022-1317-76-4-1033
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the target specificity of the transactivating factors MHBst and HBx of hepatitis B virus

Abstract: Experiments with tissue culture cells revealed that carboxy-terminaUy truncated middle surface antigen (MHBs t) and HBx of hepatitis B virus (HBV) are able to act as transcriptional transactivators (Twu & Schloemer, 1987;Wollersheim et al., 1988;Zahm et al., 1988;Caselmann et al., 1990; Kekul6 et al., 1990). The transactivating function of MHBs t and HBx is directed to many known viral and cellular enhancer and promoter elements. Synopsis of epidemiological and molecular studies led to the assumption that, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Besides activation of viral elements like the simian virus 40 (SV40) early enhancer , the LTRs of Rous sarcoma virus (RSV), human immunodeficiency virus-1 (HIV-1) and human T cell lymphotropic virus type I (HTLV-I ; Meyer et al, 1992 ;Lauer et al, 1994), stimulation of the promoter sequences of the oncogenes c-myc Natoli et al, 1992 ;Lauer et al, 1994), c-fos (Meyer et al, 1992, Natoli et al, 1992Lauer et al, 1994 ;Schlu$ ter et al, 1994) and the interleukin-6 gene (Meyer et al, 1992) has been shown. Furthermore, MHBs t mediates its transactivating effect via factors binding to the serumresponsive element (SRE), to 12-O-tetradecanoylphorbol 13-acetate-responsive elements (TREs ; Natoli et al, 1992), NF-κB- (Meyer et al, 1992 ;Natoli et al, 1992 ;Lauer et al, 1994 ;Mu$ hlbauer & Koch, 1995), AP1- (Hildt et al, 1993 ;Lauer et al, 1994 ;Mu$ hlbauer & Koch, 1995) and AP2- (Lauer et al, 1994) binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Besides activation of viral elements like the simian virus 40 (SV40) early enhancer , the LTRs of Rous sarcoma virus (RSV), human immunodeficiency virus-1 (HIV-1) and human T cell lymphotropic virus type I (HTLV-I ; Meyer et al, 1992 ;Lauer et al, 1994), stimulation of the promoter sequences of the oncogenes c-myc Natoli et al, 1992 ;Lauer et al, 1994), c-fos (Meyer et al, 1992, Natoli et al, 1992Lauer et al, 1994 ;Schlu$ ter et al, 1994) and the interleukin-6 gene (Meyer et al, 1992) has been shown. Furthermore, MHBs t mediates its transactivating effect via factors binding to the serumresponsive element (SRE), to 12-O-tetradecanoylphorbol 13-acetate-responsive elements (TREs ; Natoli et al, 1992), NF-κB- (Meyer et al, 1992 ;Natoli et al, 1992 ;Lauer et al, 1994 ;Mu$ hlbauer & Koch, 1995), AP1- (Hildt et al, 1993 ;Lauer et al, 1994 ;Mu$ hlbauer & Koch, 1995) and AP2- (Lauer et al, 1994) binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…While there may be some detailed differences between the transactivators, such as transactivation through specific sequences of the SV40 enhancer, 198 elucidation of the mechanisms of HBVencoded proteins in carcinogenesis (LHBs, truncated HBs proteins, and HBx protein) shows a multifunctional role of these proteins: interference with cellular mechanisms is both through transcriptional mechanisms (modulating TBP, TFIIH-activity, altering the binding specificity of transcription factors) and through the modulation of signaling cascades (NFΚB activation, AP1 activation). Furthermore, cellular anti-tumor pathways (p53, nucleotide excision repair, apoptosis) are directly influenced by these transactivators.…”
Section: Relevance In Tumorigenesismentioning
confidence: 99%